Dietary cholesterol supplementation and inhibitory factor 1 serum levels in two dizygotic Smith-Lemli-Opitz syndrome twins: a case report - Maurizio Delvecchio; Biagio Rapone; Simonetta Simonetti; Simona Fecarotta; Graziana De Carlo; Elvira Favoino; Maria Teresa Loverro; Anna Maria Isdraele Romano; Federica Taurino; Edoardo Di Naro; Antonio Gnoni (BMC, 2020)
Abstract Background Smith-Lemli-Opitz syndrome (SLOS) is a rare genetic neurodevelopmental disorder caused by the defect in the 7-dehydrocholesterol reductase. This defect leads to the deficiency of cholesterol biosynthesis with accumulation of 7-dehydrocholesterol. Inhibitory factor 1 (IF1) is a well-known mitochondrial protein. Recently, it has been discovered in the human serum where it is reported to be involved in the HDL-cholesterol intake. Here we report the IF1 presence in the serum of two paediatric SLOS dizygotic twins treated with dietary cholesterol supplementation. Case presentation The patients showed a typical phenotype. They started dietary supplementation with cholesterol when 2 months old. The cholesterol intake was periodically titrated on the basis of weight increase and the twin 1 required a larger supplementation than the twin 2 during the follow-up. When 6.4-year-old, they underwent IF1 assay that was 7-fold increased in twin 2 compared to twin 1 (93.0 pg/ml vs 13.0 pg/ml, respectively). Conclusions We report, for the first time, the presence of circulating IF1 in the serum of SLOS patients, showing different levels among them. Our findings confirm that IF1 could be a novel research target in cholesterol-related disorders and also in SLOS, and could contribute to the general debate on IF1 as a new modulator of cholesterol levels.